Towards worldwide height system unification using ocean information - Woodworth P.L.; Hughes C.W.; Bingham R.J.; Gruber T. (Journal of Geodetic Science, 2012)
We describe the application of ocean levelling to worldwide height system unification. The study involves a comparison of ‘geodetic’ and ‘ocean’ approaches to determination of the mean dynamic topography (MDT) at the coast, from which confidence in the accuracy of stateof- the-art ocean and geoid models can be obtained. We conclude that models are consistent at the sub-decimetre level for the regions that we have studied (North Atlantic coastlines and islands, North American Pacific coast and Mediterranean). That level of consistency provides an estimate of the accuracy of using the ocean models to provide an MDT correction to the national datums of countries with coastlines, and thereby of achieving unification. It also provides a validation of geoid model accuracy for application to height system unification in general. We show how our methods can be applied worldwide, as long as the necessary data sets are available, and explain why such an extension of the present study is necessary if worldwide height system unification is to be realised.